RUSLE-based erosion analysis and its contribution to flooding in Kota Belud, Sabah - Amirah Saidin; Kamilia Sharir; Dwa Desa Warnana; Wien Lestari; Rodeano Roslee (International Information and Engineering Technology Association (IIETA), 2025)
Erosion and flooding are closely linked processes that influence each other through sediment transport and hydrological changes. Erosion reduces the capacity of river channels by depositing sediment, while flooding accelerates soil detachment and transport. In Kota Belud, Sabah, this interplay is intensified by deforestation, agricultural activities, and unsustainable land development. This study employs the Revised Universal Soil Loss Equation (RUSLE) within a GIS environment to assess erosion prone areas and their contribution to flooding. A 5 m × 5 m resolution Digital Elevation Model (DEM) was used to derive the LS factor, while rainfall data, soil series, and land cover were used to compute the R, K, and C factors, respectively. The model was validated using flood-prone area data through an Area Under the Curve (AUC) analysis, resulting in an accuracy of 81.22%, indicating good predictive capability. The erosion susceptibility map revealed that 83.6% of the area has very low susceptibility, while 0.5% falls under high to very high categories. These critical zones likely contribute to sedimentation in rivers, exacerbating downstream flooding. The findings provide essential insights for regional flood management, emphasizing the need for targeted soil conservation and sustainable land-use planning in Kota Belud.